2002
DOI: 10.1111/j.1471-0528.2002.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, provider and sociodemographic predictors of late initiation of antenatal care in England and Wales

Abstract: There is a pressing need for further research to identify the specific concerns of late bookers, to identify areas where new interventions might encourage the uptake of services and to gauge the likely impact of increased dissemination of information about the availability of antenatal care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 34 publications
7
48
0
1
Order By: Relevance
“…Our findings differ with the reports from studies in most developed countries where the odds for late initiation of antenatal care have been reported as higher in women with social and financial disadvantages like teenage pregnancy, unemployment, single women and black women. 12,13,17 Analysis of Socioeconomic class showed that a quarter of the women belonged to the upper social class. The social classification used in this study combined the woman's level of education and the husband's occupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings differ with the reports from studies in most developed countries where the odds for late initiation of antenatal care have been reported as higher in women with social and financial disadvantages like teenage pregnancy, unemployment, single women and black women. 12,13,17 Analysis of Socioeconomic class showed that a quarter of the women belonged to the upper social class. The social classification used in this study combined the woman's level of education and the husband's occupation.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 While studies from most developed countries have established that socially disadvantaged women such as teenagers ,unmarried women and women with lower level of education and lower socioeconomic class are more likely to book late for antenatal care, studies from sub-Saharan Africa suggest that these may not be the major determinants in Afri-can women. 12,13 Previous studies from Nigeria are inconclusive. While some workers found no statistically significant effect of age, parity, level of education and socioeconomic class as well as incidence of previous obstetric complications between women who registered early and those who booked late, others have reported these as significant.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The timing of prenatal care initiation can be influenced by numerous prepregnancy factors, including maternal educational attainment, [1][2][3][4][5][6] age, [1][2][3][4][5][6][7][8] parity, 2,6,7 ethnicity, 3 women's feeling about pregnancy and prenatal care, 6 and insurance. 2,[8][9][10][11] In the last two decades, some investigators have demonstrated the importance of preconceptional care to improve perinatal outcomes. For example, it has been demonstrated that addressing periconceptional folic acid use at a preconceptional consultation improves folate use among women planning to conceive.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this, most studies dealing with prenatal care or the lack there of have focused on the maternal aspect, investigating the determinants of late care, characteristics of women with late care, racial disparities and the utilization of available prenatal services [12][13][14][15]. Furthermore, studies investigating neonatal outcomes focus almost exclusively on prematurity, low birth weight, and neonatal mortality [16][17][18].…”
Section: Introductionmentioning
confidence: 99%